Hospital Presentations of Acute Diverticulitis During COVID-19 Pandemic may be More Likely to Require Surgery due to Increased Severity: A Single-Centre Experience. Issue 1 (January 2022) - Hossain, Naveed; Naidu, Vishnu; Hosny, Shady; Khalifa, Mohamed; Mathur, Pawan; Al Whouhayb, Maitham
Background: The novel coronavirus disease 2019 (COVID-19) pandemic has resulted in fewer emergency presentations of many acute medical and surgical conditions. The purpose of this study was to assess the severity of disease at presentation and quantify the change in number of presentations during this period. Methods: This retrospective study includes all patients diagnosed with acute diverticulitis on abdominopelvic computerised tomography (CT) between March 1, 2020 and June 30, 2020, compared to the same period in 2019. Follow up scans on the index admission were excluded. Hinchey grade was assessed for all CT scans. Inflammatory markers were analysed, along with outcome measures including length of stay and mortality. Results: Acute diverticulitis was diagnosed in 52 CT scans in the acute pandemic period – a decrease of 51.4%. Average age at presentation was unchanged (63.3 ± 14.3 vs. 62.8 ± 13.8, P = .848). The number of Hinchey II, III and IV presentations were significantly higher in the acute pandemic period (28.8% vs. 11.2%, P = .005) and significantly more emergency operations were carried out (7.69% vs. .93%, P = .04). Mortality was not significantly increased, nor were serum levels of C-reactive protein, white cell count and lactate. Discussion: During the COVID-19 pandemic, fewer patients presented and were diagnosed with acute diverticulitis. A significantly greater proportion presented at a more advanced stage and required emergency surgery, suggesting late presentation. Our findings support the need for maintaining acute surgical services and the provision of early radiological and surgical input in patients presenting with signs and symptoms of acute diverticulitis in future pandemics.